The Use of Micro-needling with Therapeutic Agents for Tissue Regeneration - Courtney Morrow; Hannah Grach; Trina Hutto, RDH, MS, EdD (Elsevier, 2024)
OBJECTIVES: The purpose of this literature review is to analyze the current body of literature regarding the use of microneedling with a therapeutic agent, to encourage tissue regeneration and gingival health in the periodontium. METHODS: The database used for this literature review was Google Scholar with Augusta University Library accessible articles. The keywords used to find these articles were micro-needling, tissue regeneration, periodontal tissue attachment, guided tissue regeneration, and therapeutic agents. The mesh terms used were needles, periodontitis, tissues, regeneration, and epithelial attachment with the word "AND" between. Articles that were older than five years were filtered out, leaving 428 articles. Then irrelevant articles were manually filtered out. Six articles were then selected, with one of the articles being a literature review used for background information. RESULTS: Each article reviewed showed how micro-needling with therapeutic adjuncts can have a positive effect on the gingiva. These effects range from increased interdental papilla height, increased gingival thickness and collagen formation, decreased inflammation, and decreased severity of the destruction of the periodontal tissues. Micro-needling initiates a natural wound-healing process in the gingiva, and with the help of different therapeutic agents, positive results can be observed. CONCLUSIONS: Each of the articles selected used a different agent and a different micro-needling procedure. The patient's needs and wants are determining factors in which therapeutic agent would be used to assist the micro-needling procedure. Future research is needed to compare additives and procedures, in addition to micro-needling. More long-term studies are necessary to determine the lasting effects on the periodontium and overall health of the patient. In conclusion, micro-needling seems to be a cost-effective, non-invasive treatment with noticeable improvement for tissue regeneration and gingival health, proving to show validity and worth in becoming an accepted practice and treatment option in dentistry. IMPLICATIONS: Micro-needling with a therapeutic adjunct is an efficient way for dental practices to incorporate a minimally invasive treatment into a wide variety of different treatment regimens.